Implementasi Teknik Motivational Interviewing Untuk Meningkatkan Motivasi Mengaji Pada Remaja Di Desa Geramat Kabupaten Lahat - Sandi , Robbi Kurnia; Kusnadi, Kusnadi; Noviza , Neni (Jurnal Ilmu Sosial, Humaniora dan Seni, 2023)
This research is entitled Implementation of Motivational Interviewing Techniques to Increase Motivation. The aim of this research is to determine the motivation for reciting the Koran among teenagers in Geramat Village, Lahat Regency before being given the Motivational Interviewing technique. The research method used is a qualitative research method, data from this research comes from primary data and secondary data, with data collection techniques namely through interviews, observation and documentation. Meanwhile, data analysis uses descriptive analysis. The results of this research are motivation for reciting the Koran among teenagers in Geramat Village, Lahat Regency before being given the Motivational Interviewing technique. When teenagers' motivation before being given motivational interviewing techniques, teenagers' motivation is very low. Behaviors that often arise in teenagers are, feeling lazy and bored when completing assignments, not being confident, giving up easily, not paying attention to teacher instructions, not asking anyone for help, not being serious, often daydreaming, not responding to teacher advice, not answering questions. teachers, are more silent, easily discouraged and always avoid tasks.